1951
DOI: 10.2307/1538545
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Utilization by Diatoms

Abstract: Routine measurements of inorganic phosphorus concentration are frequently made on standard oceanographic stations to ascertain the potential productivity of marine waters. In quantitative, ecological studies on diatom populations in the Atlantic Ocean, Riley, Stommel and Bumpus (1949) have utilized the phosphate concentration as a nutrient index. Their equation of productivity depends upon the experimental results of Ketchum (1939), who found that phosphate concentrations helow 0.55 microgram-atoms per liter l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1954
1954
1999
1999

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 4 publications
0
17
0
1
Order By: Relevance
“…It is present in all the major food constituents and should therefore give a good idea of the assimilationbut some caution is necessaryin interpreting the results. It has been shown by various workers (Kamen & Spiegelman, 1948;Gest & Kamen, 1948;Goldberg, Walker & Whisenand, 1951;Rice, 1953) that when algae are grown in phosphate-rich media, some of the phosphorus in the culture organisms maybe labile or verylooselybound. Rice has shownthat in cultures with low P concentrations, only about 2 % is exchangeableafter they are a week old.…”
Section: Methodsmentioning
confidence: 99%
“…It is present in all the major food constituents and should therefore give a good idea of the assimilationbut some caution is necessaryin interpreting the results. It has been shown by various workers (Kamen & Spiegelman, 1948;Gest & Kamen, 1948;Goldberg, Walker & Whisenand, 1951;Rice, 1953) that when algae are grown in phosphate-rich media, some of the phosphorus in the culture organisms maybe labile or verylooselybound. Rice has shownthat in cultures with low P concentrations, only about 2 % is exchangeableafter they are a week old.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the phosphorus contained in the phytoplankton can be readily hydrolyzed, whereas in the calanuses it is tightly bound and requires more rigid hydrolysis for its release (Goldberg et al 1951, Conover 1961, Parsons et al 1977. The latter are most predominant in bones of animals, chitinous exoskeletons and scales.…”
Section: Phosphorus In Marine Organisms Regeneration Of Phosphorusmentioning
confidence: 99%
“…Recently, Rediske and Selders (10) reported the uptake of strontium by plants to be proportional to the concentration of this element in the nutrient solution. Goldberg et al (5), working with diatoms, found the phosphate uptake to be proportional to the concentration in the medium over the range 0.5 to 3.5 ,ug/l. Similar findings were reported by Ketchum (7).…”
mentioning
confidence: 99%